GENE ACTION AND HERITABILITY ESTIMATES OF QUANTITATIVE CHARACTERS AMONG LINES DERIVED FROM VARIETAL CROSSES OF SOYBEAN - Lukman Hakim; Suyamto Suyamto (Indonesian Journal of Agricultural Science, 2017)
The knowledge of genetic action, heritability and genetic variability is useful and permits plant breeder to design efficient breeding strategies in soybean.  The objectives of this study were to determine gene action, genetic variability, heritability and genetic advance of quantitative characters that could be realized through selection of segregation progenies. The F1 population and F2 progenies of six crosses among five soybean varieties were evaluated at Muneng Experimental Station, East Java during the dry season of 2014.  The lines were planted in a randomized block design with four replications.  The seeds of each F1 and F2 progenies and parents were planted in four rows of 3 m long, 40 cm x 20 cm plant spacing, one plant per hill. The result showed that pod number per plant, seed yield, plant yield and harvest index were found to be predominantly controlled by additive gene effects.  Seed size was also controlled by additive gene effects, with small seed dominant to large seed size.  Plant height was found to be controlled by both additive and nonadditive gene effects.  Similarly, days to maturity was due mainly to additive and nonadditive gene effects, with earliness dominant to lateness.  Days to maturity had the highest heritability estimates of 49.3%, followed by seed size (47.0%), harvest index (45.8%), and pod number per plant (45.5%).  Therefore, they could be used in the selection of a high yielding soybean genotype in the F3 generation.